Response to: DNA identification by pedigree likelihood ratio accommodating population substructure and mutations - Egeland, Thore (BioMed Central, 2011)
Mutation models are important in many areas of genetics including forensics. This letter criticizes the model of the paper 'DNA identification by pedigree likelihood ratio accommodating population substructure and mutations' by Ge et al. (2010). Furthermore, we argue that the paper in some cases misrepresents previously published papers. Please see related letter: http://www.investigativegenetics.com/content/2/1/8.